ANALYSIS OF FACTORS AFFECTING STOCK PRICES THROUGH CAPITAL ADEQUACY LEVEL IN CONVENTIONAL COMMERCIAL BANKS LISTED ON INDONESIA STOCK EXCHANGE IN 2015-2017 - Wulandari, Desy (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to examine whether there is an effect of loan to deposit ratio (LDR), non-performing loans (NPL), return on assets (ROA), net interest margin (NIM), operational expenses on operating income (BOPO) and good corporate governance (GCG) both directly and indirectly through the Capital Adequacy Level (CAR) of the Share Price. This study aims to examine whether there is an effect of loan to deposit ratio (LDR), non-performing loans (NPL), return on assets (ROA), net interest margin (NIM), operational expenses on operating income (BOPO) and good corporate governance ( GCG) both directly and indirectly through the Capital Adequacy Level (CAR) of the Share Price. Data is processed using Path Analysis. The results of this study indicate that Non-Performing Loans (NPL), Return On Assets (ROA), Net Interest Margin (NIM) have a direct positive effect on stock prices. While the Loan to Deposit Ratio (LDR), Operating Expenses on Operating Income (BOPO), Good Corporate Governance (GCG) have a significant negative direct effect on Stock Prices. Hypothesis testing for indirect effect shows the results that the Loan to Deposit Ratio (LDR), Non-Performing Loans (NPL), Return On Assets (ROA), Net Interest Margin (NIM), Operational Expenses on Operating Income (BOPO), and Good Corporate Governance (GCG) has a significant effect on Stock Prices through the Capital Adequacy Level (CAR).